PERAN KEPOLISIAN DALAM MENCEGAH DAN MENANGGULANGI KEKERASAN SEKSUAL TERHADAP ANAK DI KOTA SORONG : Studi Kasus Polresta Sorong Kota - Rahmi, Aulia (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2024)
This article discusses the role of the police in preventing and dealing with cases of sexual violence against children in Sorong City. The rampant violence that occurs in Sorong City, one of which is sexual violence against children, this is proven from data that the author took directly at the PPA Unit of the Sorong City Police Criminal Investigation Unit. In efforts to prevent and deal with cases of sexual violence, the police use two approaches, namely preventive and repressive approaches. Apart from that, this research also explains the factors that cause sexual violence against children and what obstacles the police have in preventing and dealing with cases of sexual violence, as well as the impact of sexual violence against minors.